Experimental study of properties and fabrication of three-dimensionally ordered macroporous tin (IV) oxide films for application on dye-sensitized solar cells - Khor, Mei Lian. (2010)
This report presents a three-dimensionally ordered macroporous (3DOM) colloidal templating technique for tin (IV) oxide in order to study and investigate its effect on the fabrication of dye-sensitized solar cells. This proposed structure would be a modification to the common architectural structures such as nanowires, nanoparticles and traditional bulk titanium dioxide and was expected to increase the efficiency of the DSSCs. 3DOM promised a higher surface area to volume ratio and with the highly porous and nanometer-scale macropores, electron diffusion length was expected to be reduced and hence higher charge transfer rate which can in turn, result in higher photovoltage. On the other hand, Tin (IV) oxide was studied to address the shortcomings and replace the conventional wide band-gap semiconducting oxide material, titanium dioxide.